Ultraviolet Raman spectroscopy of graphene and transition‐metal dichalcogenides. Issue 11 (13th August 2015) - Saito, Riichiro; Nugraha, Ahmad R. T.; Hasdeo, Eddwi H.; Siregar, Syahril; Guo, Huaihong; Yang, Teng
Abstract: Here, we overview Raman spectroscopy of graphene and transition‐metal dichalcogenides as a function of laser excitation energy E L, especially in the ultraviolet (UV) region. The double resonance G ′ (or 2D) band of graphene is calculated for the laser energy range up to 7 eV. The intensity of the G ′ band is proportional to E L − 1 for E L ≤ 5 eV. We also discuss electronic Raman spectra and the asymmetric Breit–Wigner–Fano lineshape of the G band in graphene for UV light. Finally, transition‐metal dichalcogenide materials show a strong optical absorption of the UV light at the M point at which we expect a two‐dimensional van Hove singularity of density of states. The double‐resonance Raman spectra for the UV light can be assigned to a combination or overtone phonons at the M point. Equi‐energy contour of initial (blue line) and intermediate (red line) states in a double‐resonance Raman process for (a) E L = 3.49 eV and (b) E L = 6.00 eV. In the case of E L = 6.00 eV, the blue and red lines are almost overlapped on each other. Gray‐shaded areas are possible phonon wave vectors for the double‐resonant Raman process that are measured from the center of the Brillouin zone. Abstract : Saito et al. calculate G′ band Raman intensities of graphene as a function of laser energy E L in the range of visible light to deep ultraviolet. The G′ band peak intensity basically decreases with the increase of E L, except at around 5.08 eV, where a small jump of intensity appears. These calculations confirm that the G′ band of graphene in the UV region is hardly observed by experiment.